Regulatory Non-coding RNAs Involved in Oxidative Stress and Neuroinflammation: An Intriguing Crosstalk in Parkinson's Disease - Khish, Naser S.; Ghiasizadeh, Pooran; Rasti, Abolhasan; Moghimi, Omid; Zadeh, Arash Zeynali; Bahiraee, Alireza; Ebrahimi, Reyhane (Current Medicinal Chemistry, 2024)
Parkinson's disease (PD) is a common neurodegenerative disorder characterized by the accumulation of α-synuclein and the degeneration of dopaminergic neurons in the substantia nigra. Although the molecular bases for PD development are not fully recognized, extensive evidence has suggested that the development of PD is strongly associated with neuroinflammation. It is noteworthy that while neuroinflammation might not be a primary factor in all patients with PD, it seems to be a driving force for disease progression, and therefore, exploring the role of pathways involved in neuroinflammation is of great importance. Besides, the importance of non-coding RNAs (ncRNAs), such as microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and competing endogenous RNAs (ceRNAs), has been widely studied with a focus on the pathogenesis of PD. However, there is no comprehensive review regarding the role of neuroinflammation- related ncRNAs as prospective biomarkers and therapeutic targets involved in the pathogenesis of PD, even though the number of studies connecting ncRNAs to neuroinflammatory pathways and oxidative stress has markedly increased in the last few years. Hence, the present narrative review intended to describe the crosstalk between regulatory ncRNAs and neuroinflammatory targets with respect to PD to find and propose novel combining biomarkers or therapeutic targets in clinical settings.
Keywords: oxidative stress